2009
DOI: 10.1097/brs.0b013e31819966b0
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence Between Disc Space Height, Range of Motion and Clinical Outcome in Total Lumbar Disc Replacement

Abstract: A significant interdependence was observed between the parameters DSH, ROM and the clinical outcome following TDR. Whilst the DSH is restored, TDR leads to a significant decrease in postoperative ROM, particularly at the lumbosacral junction. Higher preoperative DSH and ROM revealed a beneficial effect on the postoperative segmental mobility. The subjective outcome evaluation indicates that TDR is a viable treatment option even in advanced stages of degenerative disc disease in the absence of other contraindic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 60 publications
2
26
0
Order By: Relevance
“…Due to the small number of patients, the results (especially the non-significant results) should be interpreted with caution. However, the radiologic factors that we found to be associated with inferior outcomes after TDR are supported by the calculations of our probabilistic FEM study and are consistent with several clinical observational studies [20,[25][26][27]. Additionally, significant results were obtained despite the use of relatively rigid statistical methods.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Due to the small number of patients, the results (especially the non-significant results) should be interpreted with caution. However, the radiologic factors that we found to be associated with inferior outcomes after TDR are supported by the calculations of our probabilistic FEM study and are consistent with several clinical observational studies [20,[25][26][27]. Additionally, significant results were obtained despite the use of relatively rigid statistical methods.…”
Section: Discussionsupporting
confidence: 89%
“…Distraction is usually necessary because the restoration of disc height after TDR is an important factor for a good clinical outcome [26,40]. However, it is difficult for the surgeon to determine the ideal degree of correction of a degenerated disc, because the optimum amount is unknown and varies individually.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zindrick et al [10] concluded in a review that there was no definitive evidence about which variables that affect outcome in disc prosthesis surgery. Siepe et al [28,29], reported better outcomes for disc surgery in younger patients, for monosegmental surgery (especially at the L4/L5 level) and in patients with lower disc height. Bertagnoli et al found better outcomes in patients with disc height [4 mm and no facet joint arthritis, and Guyer et al found that time off work before treatment predicted outcome [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Ten seconds of rest were allowed between each angle, and a passive ROM exercise was conducted 3 times to relax the lumbar extensor. The reliability of this method is r = 0.81-0.89 19) .…”
Section: Methodsmentioning
confidence: 99%